(untitled) (Revista de Crítica Literaria Latinoamericana, 2016)
Eduardo Chirinos’ (Lima, 1960-2016) poetry approaches an intertextual dialogue with the past, merging with present. In this integrating journey, he questions the scientific knowledge from its origin until today. He addresses the possibilities of conversing with accessible language, which is at the same time different, extracting poetry from words.